To the determination of the capacity descheduling coefficients of railway sections - S. Yu. Kirillova; K. Yu. Nikolaev (Вестник Научно-исследовательского института железнодорожного транспорта)
The article investigates factors arising from the use topology of the railway network and affecting the calculation and of new technologies for organizing train operation, features of the use of the available capacity of railway sections. Based on the result generalization of such actions as mass analytical calculations in the automated development of data sheets for the available capacity of the Russian Railways network, analysis of standard train schedules and building of experimental traffic schedules, it has been established that when calculating the capacity of sections with an unparalleled train schedule and sections with an intensive suburban and suburban-urban traffic one should take into account the need to ensure the continuity of trains of different categories between service stops, the mutual arrangement of trains in the clock schedule and on adjacent sections. Authors carried out an evaluation of the influence of various topology options of calculated sections on its capacity. Recommendations are given for changing the criteria for dividing railway lines into calculated sections: separately for calculating the capacity and separately for calculating the capacity descheduling coefficients. The influence of adjacent infrastructure elements on the loss of available capacity is considered when it is impossible to synchronize approaching trains with periods of free runs and station elements for its passage; recommendations are formulated for its calculation experimentally — by building intensive train schedules or simulation modelling. The calculation formulas have been developed for the train descheduling coefficients when using the clock schedule in various types of passenger traffic and the impact of the considered types of traffic on the schedule exception of the available capacity have been assessed. The research results are intended for use in regulatory and methodological documents and automated systems for calculating, analyzing the use and justifying the development of throughput and carrying capacity of railways.